Growth, Nontradables, and Price Convergence in the Baltics - Richards, Anthony (IMF Working Papers; Working Paper ;, 1995)
This paper reviews the recent real exchange rate appreciation observed in the three Baltic countries. Until now, this phenomenon may be viewed primarily as a consequence of the undervalued real exchange rates of the new currencies. Looking ahead, a tendency for continued real appreciation is to be expected as part of the transition process toward higher income levels, due in part to differential productivity growth rates in the tradable and nontradable sectors. In the absence of an appreciation of the nominal exchange rate, this real appreciation will occur through inflation rates that are higher than in industrial countries. Provided that the current prudent economic policies are continued, such higher inflation will not threaten macroeconomic objectives and may indeed be viewed as an indication that the transition process is progressing as expected.